Change management and its role in enhancing human resource potential in educational institutions: A study at Rowad Attarbiah Schools in Riyadh / Abdullah Mohammed A Alasmari - Abdullah Mohammed , A Alasmari (2019)
This study fundamentally highlights the role of Change management in promoting the human resources for the employees in the institutions in Saudi Arabia in an attempt to support the efforts of educational development as adopted in the kingdom’s vision 2030. The objective of this study is to measure the degree of correlation between the application of change strategies, as an independent factor, and the level of effectiveness and efficiency acquired by the personnel of the human resources management in the kingdom’s educational institutions, as a dependent factor. This is done by determining the extent of the impact of developing the abilities of the employees in ‘education pioneers’ schools - as a case study – through the change management strategies adopted in the schools to achieve the desired future reality. The research plan follows a mixed approach: through a descriptive analysis of the nature, strategies and stages of application of change management, understanding the nature of HRM's function, activities and tasks carried out in order to achieve its goals, and through a descriptive analysis of the correlation between the application of change strategies and the employees acquisition of skills and competencies necessary to achieve higher levels of performance. The study also used the descriptive approach by analyzing the data collected through a questionnaire directed at a random sample (250 individuals) of the employees of the ‘pioneers schools’ of civic education, within the Education Department in Riyadh Educational Region, which is comprised of 250 male and female employees in two sectors: the boys education sector which consists of three stages of education (primary, intermediate and secondary) and the girls education sector which consists of four stages of education ((preliminary, primary, intermediate and secondary). The data obtained is analyzed in order to arrive at set of conclusions that confirm the extent to which the main hypotheses of the research could be accepted or rejected. One of the most important conclusions of the research is the confirmation of the influential role of the change strategies on developing and supporting the competitive excellence of the human resource management personnel in the educational institutions, as the results of the study have shown a strong correlation between the availability of the administrative, organizational and intellectual skills of the personnel of the human resources department in the Saudi educational institutions and the rates of activation of the change management planning strategies in these institutions.